PROFIL TINGKAT PENGETAHUAN GURU BIOLOGI DI SMPN SEKOTA TERNATE TENTANG SINDROM DISLEKSIA UMUM PADA SISWA SMP - Risna Yanti; Sundari Sundari; Arini Z. N (Universitas Khairun, 2018)
Descriptive survey research has been carried out on the analysis of the level of knowledge of Biology teachers at junior high School in Ternate City about Dyslexia syndrome in junior high school students. The objective of this study was to determine the profile of the level of knowledge of Biology teachers at the SMP in Ternate about dyslexic syndrome in middle school students. The results of this study indicate that in general the level of knowledge of Biology teachers about general Dyslexic syndrome in junior high school students in Ternate in the category of Very Good, this can be seen in the teacher's answer choices most answered on a scale of 5 (strongly agree) as much as 61.3%, scale 4 (agree) as much as 24%; scale 3 (quite agree) of 8.1%; and scale 2 (disagree) of 5.6% and scale 1 (strongly disagree) of 1%. The results of this study are expected to be taken into consideration in the handling of students with special needs appropriately especially for students with problems reading difficulties at the junior high school level.Keywords: profile, knowledge, syndrome, dyslexia, difficulty, reading